Detection of hibiscus chlorotic ringspot virus, citrus exocortis viroid and citrus viroid VI in China rose from Italy using high-throughput sequencing - PARRELLA, Giuseppe; FAURE, Chantal; MARAIS, Armelle; TROIANO, Elisa; CANDRESSE, Thierry (Phytopathologia Mediterranea, 2024)
In Spring 2024, a symptomatic plant of China rose (Hibiscus rosa-sinensis) showing leaf yellowing and deformation, located in the province of Naples (South Italy), was re-sampled for further investigations. Total RNAs were purified from leaves and subjected to Illumina HTS analysis. Results confirmed that the plant was infected by hibiscus chlorotic ringspot virus (HCRSV), citrus exocortis viroid (CEVd), and citrus viroid VI (CVd-VI). The two viroids had not been previously detected in China rose. HTS results were confirmed by RT-PCR in the re-sampled plant, and in three nearby China rose plants with the same symptoms, using specific primer pairs for the three pathogens, followed by Sanger sequencing and BLAST analysis of the sequences. Different results obtained can be due to differing sensitivity and specificity in HTS-based detection of plant viruses. This is the first report of multiple infections by HCRS, CEVd and CVd-VI in China rose, which is also a new host for both of the viroids.